O rateio de ICMS por desempenho de municípios no Ceará e seu impacto em indicadores do sistema de avaliação da educação - Brandão, Júlia Barbosa (2014)
One quarter of all of the Value Added Tax (VAT) collected by Brazilian states is distributed among the municipalities. Three quarters of this transfer is based on the value added by each municipality, but states have the discretion to set their own rules to distribute the remaining quarter. Some states have (recently) changed their laws to condition the distribution on performance indicators as an incentive for better governance. In the state of Ceará all of the discretionary portion of the VAT is distributed according to a rule based on the indicators of performance in the areas of education (72%), health (20%), and environment (8%). This study aims to estimate the impact of the introduction of such rule in Ceará on municipalities performance in education, measured by the IDEB and Prova Brasil. This was done by employing the double difference method to compare the change in performance around the introduction of the new rules in municipalities in Ceará and in neighboring states. Two alternative ways to define the treatment and control groups were used, one relying on geographical proximity and the other on standard matching techniques. In addition to the basic comparison between treatment and control groups, we also separated municipalities into winners and losers of the new law, and into the best and worst GDP per capita performances. The results indicate a positive impact on both the IDEB and Prova Brasil. Even those municipalities that lost resources with the change in the VAT distribution rules have improved their performance in education. The poorer municipalities in the state, which have performed worse than the richest ones, increased their performance by decreasing the performance deficit relative to the richest municipalities. In this sense, there is evidence that the change in the VAT Law implemented by Ceará generated positive impacts in municipality performance in both IDEB and Prova Brasil.